2021
DOI: 10.1021/acs.chemmater.1c00616
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Ternary Li–Mg–Si Zintl Phase Formation and Evolution for Si Anodes in Li-Ion Batteries with Mg(TFSI)2 Electrolyte Additive

Abstract: Improved electrochemical performance of Si was recently reported by adding multivalent cation salts (such as Mg2+, Al3+, Ca2+, etc.) in the electrolyte. This is achieved via the formation in an in situ manner of relatively more stable Li–M–Si ternary phases with less chemical reactivity. These phases stabilize Si anions and thus reduce side reactions with electrolytes at the surface and eventually benefit the overall electrochemistry. To understand the mechanism of ternary Zintl phase formation and its dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Intermediate phases, identified by MAS-NMR, included various silicon oxide, hydroxide, and hydride species that effected the cycling performance due to increased surface reactivity with the electrolyte as a function of charge. Building on the ability to study amorphous and nanoscale surface coatings, it was used to evaluate the products of an in-situ synthesis method that selectively coats the surface of an active silicon particle (BH Han et al, 2019a;BH Han et al, 2021;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate phases, identified by MAS-NMR, included various silicon oxide, hydroxide, and hydride species that effected the cycling performance due to increased surface reactivity with the electrolyte as a function of charge. Building on the ability to study amorphous and nanoscale surface coatings, it was used to evaluate the products of an in-situ synthesis method that selectively coats the surface of an active silicon particle (BH Han et al, 2019a;BH Han et al, 2021;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To form a coating of these phases on the silicon in an electrochemical cell, small amounts of the salt Mg (TFSI) 2 were added to the standard Gen2 electrolyte (1.2M LiPF 6 EMC/EC 3:7). After cycling, TEM, EDX, MAS-NMR, and XPS studies showed surface Mg +2 at the approximate stoichiometric ratio of Li 14.5 Mg 0.5 Si 4 , a point in the solid solution between Li 14 MgSi 4 and Li 15 Si 4 that may represent a limit based on magnesium diffusion under the conditions used for the study (BH Han et al, 2019a;BH Han et al, 2021;Li et al, 2021). Spectroscopic evidence for interfacial phase formation is shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many composite materials act as buffering matrices for the volume expansion of silicon while simultaneously ensuring electronic contact of the active material and mechanical stability of the electrode . To avoid unwanted side reactions of the Si anode and electrolyte, suitable electrolytes matching the Si surface chemistry have to be chosen. Moreover, compounds involving Si can achieve good electrochemical performance as active anode materials: for example, silicanes and ternary Li–Mg–Si phases …”
Section: Introductionmentioning
confidence: 99%
“…7−9 Moreover, compounds involving Si can achieve good electrochemical performance as active anode materials: for example, silicanes 10 and ternary Li−Mg−Si phases. 11 Experimental lithiation of crystalline Si in a LiCl-KCl melt at a temperature of 415 °C leads to various crystalline Li x Si y phases, 12 which can be understood as Zintl-like phases. 13,14 Lithium silicide crystal structures of the compositions Li 1 Si 1 , Li 12 Si 7 , Li 7 Si 3 , Li 13 Si 4 , Li 15 Si 4 , Li 4.11 Si 1 , Li 21 Si 5 , Li 17 Si 4 , and Li 22 Si 5 (refs 15−23) have been described in the literature so far.…”
Section: Introductionmentioning
confidence: 99%